Drug Delivery: Lipid‐Modified Aminoglycoside Derivatives for In Vivo siRNA Delivery (Adv. Mater. 33/2013). (3rd September 2013) - Zhang, Yunlong; Pelet, Jeisa M.; Heller, Daniel A.; Dong, Yizhou; Chen, Delai; Gu, Zhen; Joseph, Brian J.; Wallas, Jasmine; Anderson, Daniel G.
<x xml:space="preserve">Abstract</x> The self‐assembled nanoparticles for siRNA delivery with lipid‐modified aminoglycoside derivatives is described by Daniel G. Anderson and co‐workers on page 4641. The core‐shell nanoparticles can protect siRNA from enzymatic degradation within the body and subsequently deliver siRNA into cytoplasm of target cells. The image is courtesy of Dr. Ning Zhang. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>